Security Analysis on an Optical Encryption and Authentication Scheme Based on Phase-Truncation and Phase-Retrieval Algorithm - Yi Xiong; Ravi Kumar; Chenggen Quan (IEEE Photonics Journal, 2019)
In this paper, the security of the cryptosystem based on phase-truncation Fourier transform (PTFT) and Gerchberg-Saxton (G-S) algorithm is analyzed. In this cryptosystem, the phase key generated using phase-truncated (PT) operation is bonded with the phase key generated in G-S algorithm to form the first private key, which improves the complexity of the first private key. In addition, since the second private key is generated using the G-S algorithm, the number of known constraints decreases compared to the traditional PTFT-based cryptosystem, which will lead the non-convergence of special attacks. However, it has been found that two private keys generated in the cryptosystem based on PTFT and G-S algorithm are related to one phase key generated in the G-S algorithm, which provides an additional constraint to retrieve the other private key when one private key is disclosed. Based on this analysis, two iterative processes with different constraints are proposed to crack the cryptosystem based on PTFT and G-S algorithm. This is the first time to report the silhouette problem existing in the cryptosystem based on PTFT and G-S algorithm. Numerical simulations are carried out to validate the feasibility and effectiveness of our analysis and proposed iterative processes.